Pemanfaatan Kecibeling (Strobilanthes crispa) Sebagai Obat Tradisional dan Bioaktivitasnya - Marina Silalahi (FPMIPA IKIP PGRI Bali, 2020)
Kecibeling or Strobilanthes crispa (SC) has long been used by local people as traditional medicine. This study aims to explain the relationship between the use of SC as a traditional medicine with its bioactivity so that its side effects can be minimized. The method used is a literature study published online on Google Scholar using the keywords such as: Strobilanthes crispa and bioactivities of Strobilanthes crispa. The obtained literature is synthesized so that it can explain the utilization and bioactivity of SC. The SC has beautiful flowers, so its easy to find in home yards that are used as ornamental plants or living fences. The results of ethnobotany research found that SC as a drug for wounds, treat kidney stone, treat urine system disorders, treat of appendicitis and treat of diabetes mellitus. The SC has bioactivity as anti-cancer, antidiabetic mellitus, anti-cholesterol, anti-kidney stone and anti-microbial. The bioactivity SC as an anti-cancer is more prominent and is cytotoxic against breast cancer, nasopharyngeal cancer, liver cancer and corrective cancer, therefore it can be developed as an alternative medicine in dealing with cancer.